Nordisk lexikografisk ordbok: artiklarnas struktur och innehåll - Svensén, Bo (Nordiske Studier i Leksikografi, 1995)
The project Nordic Lexicographical Dictionaiy (NLO) aims at producing a dictionaiy of Nordic lexicographical terminology, with definitions in Norwegian bokmål, and with term equivalents in five other Nordic languages as well as in English, German and French. After completing data collection and preliminary data selection, and after assigning to each concept a place in the classification scheme specially developed for NLO, the project has now reached a stage where the main task consists of making the final selection of concepts and terms and compiling the dictionary entries. This contribution presents and discusses, from various points of view, some of the entries compiled by the Swedish member of the project group.